Should I go or should I stay ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Enticing young people to stay on the land is no easy task. There is little to persuade people to stay in the village, except the village itself. The well-intentioned arguments and campaigns of their elders are, youth being youth, often rejected,...